Bromodomain inhibitor OTX015 in patients with lymphoma or multiple myeloma: a dose-escalation, open-label, pharmacokinetic, phase 1 study. Issue 4 (April 2016) - Amorim, Sandy; Stathis, Anastasios; Gleeson, Mary; Iyengar, Sunil; Magarotto, Valeria; Leleu, Xavier; Morschhauser, Franck; Karlin, Lionel; Broussais, Florence; Rezai, Keyvan; Herait, Patrice; Kahatt, Carmen; et al.
Summary: Background: The first-in-class small molecule inhibitor OTX015 (MK-8628) specifically binds to bromodomain motifs BRD2, BRD3, and BRD4 of bromodomain and extraterminal (BET) proteins, inhibiting them from binding to acetylated histones, which occurs preferentially at super-enhancer regions that control oncogene expression. OTX015 is active in haematological preclinical entities including leukaemia, lymphoma, and myeloma. We aimed to establish the recommended dose of OTX015 in patients with haematological malignancies. We report the results from a cohort of patients with lymphoma or multiple myeloma (non-leukaemia cohort). Methods: In this dose-escalation, open-label, phase 1 study, we recruited patients from seven university hospital centres (in France [four], Switzerland [one], UK [one], and Italy [one]). Adult patients with non-leukaemia haematological malignancies who had disease progression on standard therapies were eligible to participate. Patients were treated with oral OTX015 once a day continuously over five doses (10 mg, 20 mg, 40 mg, 80 mg, and 120 mg), using a conventional 3 + 3 design, with allowance for evaluation of alternative administration schedules. The primary endpoint was dose-limiting toxicity (DLT) in the first treatment cycle (21 days). Secondary objectives were to evaluate safety, pharmacokinetics, and preliminary clinical activity of OTX015. The study is ongoing and is registered withClinicalTrials.gov, numberNCT01713582 . Findings: Between Feb 4, 2013, and Sept 5, 2014, 45 patients (33 with lymphoma and 12 with myeloma), with a median age of 66 years (IQR 55-72) and a median of four lines of prior therapy (IQR 3–5), were enrolled and treated. No DLTs were observed in the doses up to and including 80 mg once a day (first three patients). We then explored a schedule of 40 mg twice a day (21 of 21 days). DLTs were reported in five of six patients receiving OTX015 at this dose and schedule (all five patients had grade 4 thrombocytopenia). We explored various schedules at 120 mg once a day but none was tolerable, with DLTs of thrombocytopenia, gastrointestinal events (diarrhoea, vomiting, dysgeusia, mucositis), fatigue, and hyponatraemia in 11 of 18 evaluable patients. At this point, the Safety Monitoring Committee decided to establish the feasibility of 80 mg once a day on a continuous basis, and four additional patients were enrolled at this dose. DLTs (grade 4 thrombocytopenia) was noted in two of the patients. In light of these DLTs and other toxicities noted at 120 mg, the dose of 80 mg once a day was selected, although on a schedule of 14 days on, 7 days off. Common toxic effects reported in the study were thrombocytopenia (43 [96%] patients), anaemia (41 [91%]), neutropenia (23 [51%]), diarrhoea (21 [47%]), fatigue (12 [27%]), and nausea (11 [24%]). Grade 3–4 adverse events were infrequent other than thrombocytopenia (26 [58%]). OTX015 plasma peak concentrations and areas under the concentration versus time curve increased proportionally with dose. Trough concentrations increased less than proportionally at lower doses, but reached or exceeded the in-vitro active range at 40 mg twice a day and 120 mg once a day. Three patients with diffuse large B-cell lymphoma achieved durable objective responses (two complete responses at 120 mg once a day, and one partial response at 80 mg once a day), and six additional patients (two with diffuse large B-cell lymphoma, four with indolent lymphomas) had evidence of clinical activity, albeit not meeting objective response criteria. Interpretation: The once-daily recommended dose for oral, single agent oral OTX015 in patients with lymphoma is 80 mg on a 14 days on, 7 days off schedule, for phase 2 studies. OTX015 is under evaluation in expansion cohorts using this intermittent administration (14 days every 3 weeks) to allow for recovery from toxic effects. Funding: Oncoethix GmbH (a wholly owned subsidiary of Merck Sharp & Dohme Corp).